2003
DOI: 10.1002/jmv.10290
|View full text |Cite|
|
Sign up to set email alerts
|

STAT1 and STAT3 α/β splice form activation predicts host responses in mouse hepatitis virus type 3 infection

Abstract: Signal transducer and activator of transcription 1alpha (STAT1 alpha) is reported to be essential for IFN-gamma and IFN-alpha regulated gene expression, while STAT1 beta, an alternate splice-form, mediates only IFN-alpha-dependent gene expression. STAT3 alpha and STAT3 beta splice forms are also differentially activated in response to cytokines including IL-6 and IL-10. The aim of this study was to investigate whether the STAT activation will predict the host immune response to viral infection and possibly a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Others have reported that treatment with antibody against TGF-␤, a known important Treg effector molecule, also resulted in prolonged survival of susceptible strains to MHV-3 infection, further supporting our hypothesis that Tregs are important in the pathogenesis of MHV-3-induced FH. 29 In addition, fgl2 ϩ/ϩ Tregs that were transferred to fgl2 Ϫ/Ϫ mice but not PEMs increased mortality to MHV-3 infection, further supporting a role for Treg-expressed FGL2 in the outcome of the infection.…”
Section: Discussionmentioning
confidence: 89%
“…Others have reported that treatment with antibody against TGF-␤, a known important Treg effector molecule, also resulted in prolonged survival of susceptible strains to MHV-3 infection, further supporting our hypothesis that Tregs are important in the pathogenesis of MHV-3-induced FH. 29 In addition, fgl2 ϩ/ϩ Tregs that were transferred to fgl2 Ϫ/Ϫ mice but not PEMs increased mortality to MHV-3 infection, further supporting a role for Treg-expressed FGL2 in the outcome of the infection.…”
Section: Discussionmentioning
confidence: 89%
“…The production of two isoforms of STAT1 expression by alternative cleavage and polyadenylation has been well described, and several lines of evidence indicate that the ratio of STAT1␤ to STAT1␣ modulates the cellular response to viral and mycobacterial infection, IFN exposure, and apoptotic stress (1,2,27,38). We have previously shown that EBV SM leads to increased total STAT1 levels, resulting in increased expression of several genes stimulated by type I IFNs (IFN-␣ and IFN-␤) (31).…”
Section: Discussionmentioning
confidence: 99%
“…STAT1␤ therefore acts as a dominant-negative repressor of STAT1␣ signaling in the IFN-␥ response (5,29,38). Consistent with a role for STAT1␤ as an antagonist of STAT1␣, the ratio of STAT1 ␣ and ␤ isoforms has been shown to affect cellular apoptosis and resistance to viral and mycobacterial infection (1,2,27). Interestingly, SM disproportionately increases the relative amounts of STAT1␤ mRNA, suggesting that SM also affects STAT1 mRNA processing (31).…”
mentioning
confidence: 81%
“…Taken together, these findings demonstrate that the biological consequences of aberrant expression and activation of STAT1 and STAT5 are governed in a cell- and context-specific manner, thereby making it difficult to draw more general conclusions about their functions in human malignancies. Moreover, and similar to STAT3, both STAT1 and STAT5 are subject to alternative splicing, events that may also contribute to their dichotomous activities in various human cancers 99 , 100 . As such, future studies need to more thoroughly interrogate the functions of STAT1 and STAT5 variants in developing and progressing carcinomas, as well as in their acquisition of EMT phenotypes.…”
Section: Other Stat Proteinsmentioning
confidence: 99%